THE BLACK CHILDREN VIEWED BY THE SOCIOLOGY OF CHILDREN IN BRAZIL: A LITERATURE REVIEW - Míghian Danae Ferreira Nunes; Lajara Janaina Lopes Corrêa (Escola Superior de Educação de Paula Frassinetti, 2016)
This article analyzes the dissertations and theses related to the research on black children and racial relations through a survey conducted in the database of the Coordination of Improvement of Higher Education Personnel (Capes), Brazilian Digital Library of Theses and Dissertations (BDTD-ibicit), and in congress sites like Congresso de Pesquisadores/as Negros/as - COPENE, among others. We chose the studies with children up to six years of age and we cataloged in this survey the academic productions related to the theme involving black children and race relations, produced in Brazil from the decade 1990 to the year 2015. From the research carried out, it is It is possible to affirm that, even in a timid manner, the junction of these areas has been gaining some space, not without tension and criticism, these produced from questions such as age category, power relations and intersectionality. Keywords: black child, race relations, sociology of childhood.